Dynamics of energy and economic transportation efficiency: An analysis of EU transportation sector - Gokgoz, Fazil; Yalcin, Engin (Wiley, 2025)
Transportation is one of the essential milestones for the economy. However, transportation is also one of the most environmentally damaging industries due to intense energy use. These contradictory effects should be balanced. In this regard, energy and economic efficiency in the transportation sector are significant targets in the European Union. To that purpose, first, we aim to assess the energy and economic efficiency of the EU members via the two-stage slack-based DEA. The results indicate that industrialized EU countries, namely Denmark, Netherlands, and Germany, perform efficiently throughout the analysis period in the developed countries group. This finding indicates that these efficient countries both use their energy sources effectively and transform these resources into economic value. Second, we perform the Tobit regression to explore the influencing factors, which are widely used to deal with censored variables. Tobit regression results indicate that economic growth, population, and foreign direct investments have a positive and significant effect on both energy and economic efficiency, whereas energy consumption structure negatively affects the efficiency of the EU countries. This study aims to contribute to the literature by integrating two-stage DEA with Tobit regression in the transportation sector, thereby presenting a comprehensive framework for analyzing efficiency and its influencing factors. Through considering results in a broader context, the research focuses on main issues for intervention, such as the necessity to instigate innovation, to form variety in energy production, as well as to reduce resource inefficiencies in the EU member states that are still in the stage of development.
Keywords: European Union; sustainability; Tobit regression; two-stage DEA; undesirable SBM-DEA